Systemic availability of lipophilic organic UV filters through dermal sunscreen exposure. (November 2019) - Hiller, Julia; Klotz, Katrin; Meyer, Sebastian; Uter, Wolfgang; Hof, Kerstin; Greiner, Annette; Göen, Thomas; Drexler, Hans
Abstract: Background: Chemical UV filters are common components in sunscreens and cosmetic products and used to protect the skin against harmful effects of sunlight like sunburn. However, the effectiveness of sunscreens in the prevention of skin cancer is in some parts still controversial. Meanwhile, questions about negative effects of the chemical UV filters on human health arise and request an effective risk assessment. Real-life exposure data in humans after application of these products are still rare. Thus, we explored whether and to what extent UV filters are absorbed through the skin into the human body. Material and methods: Plasma and urine samples from 20 healthy volunteers were collected before, during and after a real-life exposure scenario (1st application: 2 mg/cm 2 ; 2nd and 3rd (after 2 and 4 h): 1 mg/cm 2 each) using a commercial sunscreen formulation for one day. These samples were analyzed for their content of the currently prominent UV filters octocrylene and avobenzone as well as 2-cyano-3, 3-diphenylacrylic acid (CDAA) as the main octocrylene metabolite by using different liquid chromatography electrospray-ionization tandem mass spectrometric procedures. Results: Following dermal sunscreen exposure, avobenzone, octocrylene and CDAA reached concentrations up to 11 μg/L, 25 μg/L and 1352 μg/L in plasma. In urine detection rates of avobenzone and octocrylene were low while CDAA showed a high detection rate and reached up to 5207 μg/g creatinine. Kinetic models could be fitted for octocrylene and CDAA in plasma and CDAA in urine. Concentration peaks were reached between 10 and 16 h after first application and half-life periods were in the range of 1.5 to 2 days. The lipophilic UV filter octocrylene and its metabolite CDAA showed a much slower elimination than other more hydrophilic UV filters. Concordantly, the metabolite CDAA in particular showed a markedly increased renal excretion over the whole sampling period and indicated high internal exposure to OC. Discussion: Real-life sunscreen usage leads to considerable bioavailability of organic UV filters and their metabolites which is rarely seen for other environmental exposures. A combined monitoring of the parent compound and its metabolites is important to fully address internal exposure to the UV filter in humans. Considering the kinetic profiles a prolonged systemic release due to depot formation in skin and a potential accumulation through multi-day exposure is presumed. High in-vivo loads call for a critical toxicological assessment of the UV filters and their metabolites. Graphical abstract: Unlabelled Image Highlights: After real-life sunscreen exposure, lipophilic UV-filters become bioavailable. OC and CDAA show a prolonged systemic availability and renal excretion. Accumulation after repeated exposure is likely due to depot formation. Exclusive monitoring of the parent compounds underestimates the uptake.